Gender Perspectives on Nursery Rhymes Through Music Textbooks for Primary Education - García Gil, Desirée; Lizaso Azcune, Begoña (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2012)
Although it is conceived as an eminently practical subject, frequently the music specialist in Primary Education supports his teaching on a book of text which holds a great part of the musical contents that the teacher offers to the group. Inside them, it can be observed a great amount of rhythmic and melodic exercises, listenings, theoretical explanations and activities for instruments or movement which the teacher articulates his own methodology on. Among them it is necessary to emphasize the use that the musical textbooks do of the infantile songs from a historical, "folkloric" or didactic origin, used to work with diverse procedures. However, what is the paper of the feminine identity inside those songs? According to his textual content, what role does woman occupy? Is it suitable to present in a society where the gender equality should be a top priority? The present proposal analyzes the female stereotypes contained in the infantile songs on the books of music of three of the main Spanish publishing houses: SM, Santillana and Anaya. From the study, conclusions will be able to be obtained about the exposition and transmission of the feminine model which nowadays is being implanted in the school.